THE DETERMINANTS OF FIRM’S CAPITAL STRUCTURE: EVIDENCE OF SHARIAH AND NON-SHARIAH STOCK COMPANIES IN INDONESIA - Nikmah, Choirul; Suhadak, Suhadak; Kertahadi, Kertahadi; Yeh, Hsien- Hung (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2015)
AbstractThis research investigates the determinants of capital structure for firms in Indonesia from the perspective of Shariah and non-Shariah stocks. The research was conducted using 222 non financial companies that listing in Indonesia Stock Exchange (IDX) during the period of 2007 to 2012. This study tested using multiple linier regressions with panel data.The results show that firm-specific factors such as profitability and tangibility have significant negative influence on capital structure. There is no direct industry effect on capital structure but the interaction between industry type and Shariah and non-Shariah stocks do affect the determination of capital structure. In addition, the interaction between firm-specific factors and Shariah and non-Shariah stocks affects capital structure of firms in Indonesia.